Selectivity in the Reinnervation of the Lateral Gastrocnemius Muscle after Nerve Repair with Ethyl Cyanoacrylate in the Rat - Landegren, Thomas; Risling, Marten; Hammarberg, Henrik; Persson, Jonas K. (Frontiers in Neurology, 2011)
There is a need for complementary surgical techniques that enable rapid and reliable primary repair of transected nerves. Previous studies after peripheral nerve transection and repair with synthetic adhesives have demonstrated regeneration to an extent comparable to that of conventional techniques. The aim of this study was to compare two different repair techniques on the selectivity of muscle reinnervation after repair and completed regeneration. We used the cholera toxin B technique of retrograde axonal tracing to evaluate the morphology, the number and the three-dimensional location of α-motoneurons innervating the lateral gastrocnemius muscle and compared the results after repair with either ethylcyanoacrylate or epineural sutures of the transected parent sciatic nerve. In addition, we recorded the wet weight of the muscle. Six months after transection and repair of the sciatic nerve, the redistribution of the motoneuron pool was markedly disorganised, the motoneurons had apparently increased in number, and they were scattered throughout a larger volume of the spinal cord grey matter with a decrease in the synaptic coverage compared to controls. A reduction in muscle weight was observed as well. No difference in morphometric variables or muscle weight between the two repair methods could be detected. We conclude that the selectivity of motor reinnervation following sciatic nerve transection and subsequent repair with ECA is comparable to that following conventional microsuturing.